Robust Bi-Level Planning Method for Multi-Source Systems Integrated With Offshore Wind Farms Considering Prediction Errors - Jian, Qingzhi; Liu, Xiaoming; Du, Xinye; Zhang, Yuyue; Wang, Nan; Sun, Yonghui (Frontiers in Energy Research, 2022)
Considering economy, reliability and output characteristics of multiple power sources (MPS) and energy storage (ES) comprehensively, a multi-source system integrated with offshore wind farms (OWFs) and its construction cost, operating and maintenance cost model are established. The system is mainly composed of OWFs, thermal power plants, gas turbine power plants and pumped hydro storage plants. Given the economy of power system and offshore wind power accommodation, a bi-level optimal capacity configuration and operation scheduling method is proposed for multi-source system integrated with OWF clusters with the objective function of optimal total cost. Then, a robust bi-level planning method for multi-source system integrated with OWFs considering the dual uncertainty of load and offshore wind power prediction is proposed, in which the upper and lower models are solved by improved particle swarm optimization (PSO) algorithm and CPLEX solver, respectively. Based on the method, the cost-optimal capacity configuration and operation scheduling scheme of MPS and ES can be obtained. Finally, an OWF group in Shandong Province is taken as an example to validate the validity and feasibility of the proposed method.